Hurdles on the road to personalized medicine. Issue 5 (30th August 2014) - Tursz, Thomas; Bernards, Rene
Abstract : Cancer treatment is slowly shifting from an approach in which the tissue of origin and the histology were the guiding principles for the choice of chemotherapy towards a genotype‐centric approach in which the changes in the cancer genome are used to select patients for treatment with highly selective and targeted drugs. This transition has all the hallmarks of a disruptive innovation and requires major adjustments in the way that cancer is diagnosed and treated. We discuss here the hurdles on the road ahead to a more personalized treatment of cancer. Highlights: Tissue preservation must be adapted to optimize cancer genotyping. Cancer care must be concentrated in regional centers of excellence. Clinical testing of drugs in large phase III trials will become obsolete. Early detection through "liquid biopsies" can improve survival.